Effect of Ursodeoxycholic Acid on Indirect Hyperbilirubinemia in Neonates Treated With Phototherapy. Issue 1 (January 2016) - Honar, Naser; Ghashghaei Saadi, Elham; Saki, Forough; Pishva, Narjes; Shakibazad, Nader; Hosseini Teshnizi, Saeed
ABSTRACT: Background: Hyperbilirubinemia is a common neonatal problem. The present study aimed to investigate the effect of ursodeoxycholic acid in reducing indirect hyperbilirubinemia of infants under phototherapy. Methods: This double-blind randomized clinical trial was conducted on neonates with jaundice, who had received phototherapy in the hospitals affiliated with the Shiraz University of Medical Sciences in 2013. A total of 80 neonates were enrolled in the study and were randomly divided into 2 groups. The intervention group (n = 40) with indirect hyperbilirubinemia received 10 mg · kg −1 · day −1 divided every 12 hours Ursobil (capsule 300 mg) in addition to phototherapy, whereas the control group (n = 40) received only phototherapy. Total bilirubin levels were measured every 12 hours until reaching <10 mg/dL, and then phototherapy was disrupted. The duration of phototherapy was measured. The 2 groups were compared regarding total bilirubin levels at different time points and duration of phototherapy using the generalized estimating equation (GEE) test. Results: The mean of total bilirubin in the intervention group was 12 ± 1.6, 10 ± 1.1, and 9.8 ± 0.2 mg/dL 12, 24, and 48 hours after the beginning of phototherapy, respectively. On the contrary, these measures were 14.4 ± 1.3, 12.5 ± 1.4, and 10.1 ± 1.1 mg/dL in the control group, respectively, ( P < 0.05). The mean time required for phototherapy to decrease the bilirubin level to <10 mg/dL was 15.5 ± 6 and 44.6 ± 13.3 hours in the case and the control group, respectively, ( P = 0.001). Conclusions: Ursodeoxycholic acid had additive effect with phototherapy in neonates with indirect hyperbilirubinemia. This drug also reduced the time period needed for phototherapy and, consequently, decreased the hospitalization period.